The Role of English Language Support Programs on International Academic Mobility of University Students in Shandong College of Economics and Business, China - Li, Juan (Pacific International Journal, 2024)
This paper explores the pivotal role of English language support programs in shaping the international academic mobility experiences of university students at Shandong College of Economics and Business, China. Conducting a quantitative study involving 150 participants engaged in international academic mobility, the research investigates the impact of language support initiatives, identifies challenges faced by students, and gathers suggestions for program improvement. Results reveal significant improvements in English language proficiency, academic performance, and overall satisfaction among participants. Challenges encountered, including language barriers, cultural adjustment, academic rigor, and social integration, underscore the complexities of global academic experiences. Participants' suggestions for program improvement, emphasizing increased language practice opportunities, enhanced cultural preparation, additional academic support, and more social events, provide actionable insights for program refinement. This study contributes to the broader discourse on the internationalization of higher education, emphasizing the transformative potential of language support programs in fostering successful global academic mobility experiences. The findings hold implications for institutions globally seeking to optimize language support initiatives for an increasingly diverse student body and nurture globally competent citizens.